The Accuracy of the Computed Tomography Diagnosis of Acute Appendicitis: Does the Experience of the Radiologist Matter?. (March 2018) - Lietzén, E.; Salminen, P.; Rinta-Kiikka, I.; Paajanen, H.; Rautio, T.; Nordström, P.; Aarnio, M.; Rantanen, T.; Sand, J.; Mecklin, J.-P.; Jartti, A.; Virtanen, J.; et al.
Background and Aims: To assess the accuracy of computed tomography in diagnosing acute appendicitis with a special reference to radiologist experience. Material and Methods: Data were collected prospectively in our randomized controlled trial comparing surgery and antibiotic treatment for uncomplicated acute appendicitis (APPAC trial, NCT01022567). We evaluated 1065 patients who underwent computed tomography for suspected appendicitis. The on-call radiologist preoperatively analyzed these computed tomography images. In this study, the radiologists were divided into experienced (consultants) and inexperienced (residents) ones, and the comparison of interpretations was made between these two radiologist groups. Results: Out of the 1065 patients, 714 had acute appendicitis and 351 had other or no diagnosis on computed tomography. There were 700 true-positive, 327 true-negative, 14 false-positive, and 24 false-negative cases. The sensitivity and the specificity of computed tomography were 96.7% (95% confidence interval, 95.1–97.8) and 95.9% (95% confidence interval, 93.2–97.5), respectively. The rate of false computed tomography diagnosis was 4.2% for experienced consultant radiologists and 2.2% for inexperienced resident radiologists (p = 0.071). Thus, the experience of the radiologist had no effect on the accuracy of computed tomography diagnosis. Conclusion: The accuracy of computed tomography in diagnosing acute appendicitis was high. The experience of the radiologist did not improve the diagnostic accuracy. The results emphasize the role of computed tomography as an accurate modality in daily routine diagnostics for acute appendicitis in all clinical emergency settings.